1999
DOI: 10.1097/00005537-199905000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Nerve cell adhesion molecule expression in squamous cell carcinoma of the head and neck: A predictor of propensity toward perineural spread

Abstract: There is a positive correlation between the presence of N-CAM expression and perineural invasion in SCCA of the head and neck. The expression of this adhesion molecule by tumor cells may facilitate both homophilic cell-to-cell and heterophilic cell-to-substrate adhesion, thereby enabling the tumor cells to use the perineural tissues or neural cells, or both as a conduit for perineural spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 28 publications
0
40
2
1
Order By: Relevance
“…Correlation between N-CAM expression and perineural spread has been confirmed in a variety of human carcinomas. The existence of the polisialiated form of NCAM in Wilms' tumor, neuroblastoma, pituitary tumor, small cell lung cancer, gallbladder and bile duct cancer, squamous cell cancer of head and neck, and prostat cancer results in perineural invasion and agrressive metastatic behaviour with a poor clinical outcome [20][21][22][23][24][25][26][27][28] . As the expression of the polisialiated form of NCAM correlates with tumor growth and invasiveness because of its role in cell disassociation, ıt was considered to be a poor prognostic criterion in pituitary tumors and rhabdomyosarcoma [22,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between N-CAM expression and perineural spread has been confirmed in a variety of human carcinomas. The existence of the polisialiated form of NCAM in Wilms' tumor, neuroblastoma, pituitary tumor, small cell lung cancer, gallbladder and bile duct cancer, squamous cell cancer of head and neck, and prostat cancer results in perineural invasion and agrressive metastatic behaviour with a poor clinical outcome [20][21][22][23][24][25][26][27][28] . As the expression of the polisialiated form of NCAM correlates with tumor growth and invasiveness because of its role in cell disassociation, ıt was considered to be a poor prognostic criterion in pituitary tumors and rhabdomyosarcoma [22,29] .…”
Section: Discussionmentioning
confidence: 99%
“…NCAM1 expression has been correlated with the presence of perineural invasion in specimens from a variety of cancers (28)(29)(30)(31)(32)(33)(34) and has been reported to play a role in cancer progression and axon guidance (35)(36)(37)(38)(39)(40)(41). Three different shRNAs targeting NCAM1 (referred to herein as sh 1, sh 2, and sh 3, respectively) were used to generate stable cell lines in HEI-286 Schwann cells, and Western blot and immunofluorescence analysis revealed that sh 1 and sh 2 caused strong depletion, while sh 3 led to intermediate depletion of the 140-kDa NCAM1 isoform ( Figure 9A and Supplemental Figure 7A).…”
Section: Depletion Of Ncam1 In Schwann Cells Decreases Cancer Cell Inmentioning
confidence: 99%
“…These studies are based on correlations between NCAM1 expression in cancer cells, as seen in histologic specimens, and perineural invasion (29)(30)(31)(32)(33). Elevated NCAM1 expression has also been reported in nerves at sites of perineural invasion (48).…”
Section: Ncam1 Expression In Schwann Cells Promotes Perineural Invasionmentioning
confidence: 99%
“…Tumor cells co-existence of different subsets, or transfer capability of different subsets of cells mixed with low capacity to transfer cells showed strong ability of invasion and metastasis, the reason may be related to different subsets between the degradation of extracellular matrix components and complementary role of the enzyme, changed the ability to transfer (McLaughlin et al, 1999). Loss and reduce the adhesion of tumor metastasis to obtain the first step.…”
Section: Discussionmentioning
confidence: 99%